2016
DOI: 10.1681/asn.2015050570
|View full text |Cite
|
Sign up to set email alerts
|

CKD Progression and Mortality among Hispanics and Non-Hispanics

Abstract: Although recommended approaches to CKD management are achieved less often in Hispanics than in non-Hispanics, whether long-term outcomes differ between these groups is unclear. In a prospective longitudinal analysis of participants enrolled into the Chronic Renal Insufficiency Cohort (CRIC) and Hispanic-CRIC Studies, we used Cox proportional hazards models to determine the association between race/ethnicity, CKD progression (50% eGFR loss or incident ESRD), incident ESRD, and all-cause mortality, and linear mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 42 publications
1
37
1
1
Order By: Relevance
“…Odds ratios were calculated per 1 SD deviation decrease in subscale score. Based on existing literature, potential confounding variables included age, sex, education, income, insurance status, Hispanic/Latino background, hypertension, diabetes, eGFR, and albuminuria ( Lora et al, 2011 ; Lora et al, 2009 ; Norris and Nissenson, 2008 ; Hemmelgarn et al, 2010 ; Fischer et al, 2016 ). We evaluated age, sex, and education as effect modifiers of the association between acculturation and kidney function.…”
Section: Methodsmentioning
confidence: 99%
“…Odds ratios were calculated per 1 SD deviation decrease in subscale score. Based on existing literature, potential confounding variables included age, sex, education, income, insurance status, Hispanic/Latino background, hypertension, diabetes, eGFR, and albuminuria ( Lora et al, 2011 ; Lora et al, 2009 ; Norris and Nissenson, 2008 ; Hemmelgarn et al, 2010 ; Fischer et al, 2016 ). We evaluated age, sex, and education as effect modifiers of the association between acculturation and kidney function.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies reported higher risk of CKD progression for Pacific Islanders -1 study reporting adjusted OR (95% CI): 1. [15,25,26,31,38,52]. One study reported similar risk [9].…”
Section: Pacific Islandersmentioning
confidence: 97%
“…Overall, most (n = 24) studies reported higher risk of CKD progression in African-American/Afro-Caribbean [13][14][15][16][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, some (n = 12) studies found no significant ethnic differences in risk of CKD progression, which may be partly due to smaller study sample size, duration of follow up, and/or adjustment for confounders and mediators [9,[38][39][40][41][42][43][44][45][46][47][48]. Studies adjusted for demographics factors (such as age and sex, with fewer studies adjusting for socioeconomic status), biological factors (such as baseline estimated glomerular filtration (eGFR) levels, proteinuria, baseline creatinine, cholesterol, haemoglobin, blood pressure), comorbidities (hypertension, diabetes, cardiovascular disease).…”
Section: Ethnic Differences In Ckd Progression African-americans and mentioning
confidence: 99%
“…[10,11] They account for a nearly 40% higher prevalence rate of ESKD than non-Hispanic whites and may experience increased risk of progression to ESKD. [12] , [13] In the Hispanic Community Health Study/Study of Latinos (HCHS/SOL), a prospective study of over 16,000 individuals throughout the U.S., the prevalence of CKD in all women (aged 18-74 years) was 13% and disease unawareness for men and women combined reached 18%. [14] Given the above, disease unawareness and lack of treatment could be particularly detrimental for Hispanic/Latino women of reproductive age.…”
Section: Introductionmentioning
confidence: 99%